One‐Step Fabrication of Bio‐Compatible Coordination Complex Film on Diverse Substrates for Ternary Flexible Memory - Sun, Wu‐Ji; Zhao, Yong‐Yan; Zhou, Jin; Cheng, Xue‐Feng; He, Jing‐Hui; Lu, Jian‐Mei (Chemistry : a European journal, 2019)
Recently, resistance random access memories (RRAMs) have been studied extensively, because the demand for information storage is increasing. However, it remains challenging to obtain a flexible device because the active materials involved need to be nontoxic, nonpolluting, distortion‐tolerable, and biodegradable as well adhesive to diverse flexible substrates. In this paper, tannic acid (TA) and an iron ion (FeIII) coordination complex were employed as the active layer in a sandwich‐like (Al/active layer/substrate) device to achieve memory performance. A nontoxic, biocompatible TA‐FeIII coordination complex was synthesized by a one‐step self‐assembly solution method. The retention time of the TA‐FeIII memory performance was up to 15 000 s, the yield up to 53 %. Furthermore, the TA‐FeIII coordination complex can form a high‐quality film and shows stable ternary memory behavior on various flexible substrates, such as polyethylene terephthalate (PET), polyimide (PI), printer paper, and leaf. The device can be degraded by immersing it in vinegar solution. Our work will broaden the application of organic coordination complexes in flexible memory devices with diverse substrates. Flexible memory: Tannic acid (TA) and an iron (FeIII) coordination complex were employed as an active layer in a sandwich‐like (Al/active layer/substrate) device to achieve memory performance. A nontoxic, biocompatible TA‐FeIII coordination complex was synthesized by a one‐step self‐assembly solution method. This complex can form a film on various flexible substrates (PET, PI, paper, and leaf) and all display ternary memory performance (see graphic).